Conserved characteristics of ocular refractive development – Did the eye evolve once?. (June 2019) - Sivak, Jacob G.; Sivak, Jeremy M.
Abstract: It has been speculated that the unitary eyes of vertebrates and molluscs, and the compound eyes of insects and crustaceans, evolved separately. On the other hand, the common use of rhodopsin as a photoreceptor molecule, and the conservation of Pax6 as a master control gene for eye development, suggest instead that the eye evolved once. Yet, recently the molecular genetics that had seemed to suggest a definitive answer to this evolutionary point has once again become cloudy. Here we propose an alternative approach to addressing the question of eye evolution through comparative analyses of physiological optics. Serendipitous discoveries involving form deprivation and defocusing with young monkeys and chicks demonstrated the conserved importance of visual experience on eye development. Similar results have been demonstrated in teleosts, although differences exist in eye anatomy, physiology and optics. In particular, since fish grow throughout life, these effects can also be demonstrated in adults. In comparison, the cephalopod eye is an often-cited example of convergent evolution with the vertebrate eye, although considerable developmental differences exist. Nevertheless, squid eyes from animals raised under alternative lighting exhibit anatomical and refractive changes that agree with those found in vertebrates. Together, these observations provide functional and structural support for the view that the eye evolved once. Because of their very compressed lifespans (only one to two years) cephalopods may be ideal animal models for the study of ocular refractive development. Highlights: There is continued controversy around the evolutionary origin of the eye. Studying comparative ocular refractive development may shed new light on this point. Evidence of a conserved refractive development mechanism supports a common origin for the eye. Due to their rapid growth, cephalopods may be ideal models to study ocular refractive development.